1985
DOI: 10.1080/03014468500007831
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of family resemblance for cranio-facial traits in Andhra Pradesh nuclear families and twins

Abstract: Path analysis of 12 cranio-facial measurements from a sample of nuclear families and twins from Andhra Pradesh, India is used to test hypotheses about the familial transmission of these traits. For bigonial breadth and ear dimensions, the transmission from parent to child is consistent with simple autosomal polygenic inheritance, but length, breadth and circumference of the head, facial breadth and nose dimensions show evidence of transmission in excess of polygenic expectations. Additional non-transmissible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Estimation of heritabilities through the variance components approach yielded a wide range of heritabilities (25%-61%) for 23 anthropometric phenotypes, and most of them were significant. Overall, most of these anthropometric phenotypes exhibited moderate (30%-40%) heritabilities, while some of these heritability estimates were relatively low compared to those in other studies in the literature (Devi and Reddy 1983;Poosha et al 1984;Byard et al 1985b).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Estimation of heritabilities through the variance components approach yielded a wide range of heritabilities (25%-61%) for 23 anthropometric phenotypes, and most of them were significant. Overall, most of these anthropometric phenotypes exhibited moderate (30%-40%) heritabilities, while some of these heritability estimates were relatively low compared to those in other studies in the literature (Devi and Reddy 1983;Poosha et al 1984;Byard et al 1985b).…”
Section: Discussionmentioning
confidence: 64%
“…This data-collection strategy is also necessary in societies such as India, where opposite-sex contact is generally not allowed. For example, Mueller and Titcomb (1977), Poosha et al (1984), and Byard et al (1985aByard et al ( , 1985b have used a similar method of data collection.…”
Section: Study Populationsmentioning
confidence: 99%
“…However, recent studies on the subject indicate that head circumference transmissibility can be fitted into a simple polygenic model with no evidence of common sibiling environmental influence (Poosha et al, 1984). Body height and weight transmissibility are also consistent with the most parsimonious model of only polygenic inheritance (Byard et al, ,1985aMagnus, 1984, Mangnus et al, 19841, although some form of a common environment component for all three morphometriccharacters is probably also implicated (Byard et al, ,1985b. Thus the results of our analyses clearly point to the possibility of existence of two genetic (transmissibility) subsystems, determiningfirst, early postnatal stages of human ontogeny, and second, later phases of child development.…”
Section: Principal Component Analysismentioning
confidence: 78%
“…All other facial measurements (bizygomatic breadth, total facial height, and nasal height, depth, and breadth) were influenced by common sibling environment, cultural inheritance, marital resemblance, and measurement error. Byard et al [1985b] studied the same families as Poosha et al [1984], but included twin sibs in their analysis. This investigation indicated that all of the measurements showed family resemblance.…”
Section: Literature Reviewmentioning
confidence: 99%